2013
DOI: 10.1111/liv.12365
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonaemia induces hepatic injury with alteration of gene expression profiles

Abstract: This study demonstrates that hyperammonaemia can directly induce hepatic injury via the hepatocyte apoptosis. Gene expression profile may provide the possible explanations and mechanisms for the hepatic injury induced by hyperammonaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
2
28
0
2
Order By: Relevance
“…In addition to the impact on HSC contraction, elevated ammonia has been shown to promote liver injury through up-regulation of toll-like receptor genes, generation of oxidative stress through activation of resident macrophages and neutrophils and activation of NFκB and iNOS. In addition, ammonia promotes increased hepatocyte apoptosis and changes in cell cycle with higher cyclin D1, thereby further promoting liver injury as liver disease evolves (Jia et al, 2014). It is possible that impaired urea cycle metabolism and reduced liver clearance of ammonia primes the liver and other organs to the impact of acute inflammation and further oxidative stress, as occurs in conditions such as acute-on-chronic liver failure, though this assertion requires mechanistic evaluation.…”
Section: Livermentioning
confidence: 99%
“…In addition to the impact on HSC contraction, elevated ammonia has been shown to promote liver injury through up-regulation of toll-like receptor genes, generation of oxidative stress through activation of resident macrophages and neutrophils and activation of NFκB and iNOS. In addition, ammonia promotes increased hepatocyte apoptosis and changes in cell cycle with higher cyclin D1, thereby further promoting liver injury as liver disease evolves (Jia et al, 2014). It is possible that impaired urea cycle metabolism and reduced liver clearance of ammonia primes the liver and other organs to the impact of acute inflammation and further oxidative stress, as occurs in conditions such as acute-on-chronic liver failure, though this assertion requires mechanistic evaluation.…”
Section: Livermentioning
confidence: 99%
“…The toxicity of ammonia is a result of its direct effect on pH, membrane potential and metabolism which independently or collectively cause cell dysfunction (Lai and Cooper 1991;Bosoi and Rose 2009). As the effects of ammonia are not brain-specific (Lai and Cooper 1991;Norenberg 2003), it has been shown that elevated concentrations of ammonia can also affect other organs and tissues (Kubota et al 2004;Jia et al 2014;Rose 2014).…”
Section: +Hsdwlf Hqfhskdorsdwk\ Dqrwkhu Frpsolfdwlrq Ri Olyhu Glvhdvhmentioning
confidence: 99%
“…In addition to the well‐known neurotoxic effects, hyperammonemia has a deleterious effect on several organ systems, which may augment inflammation and/or organ injury . Hyperammonemia may directly induce hepatic injury, potentiate immune dysfunction and hepatic stellate cell activation, and contribute to the pathogenesis of sarcopenia, which is an independent predictor of mortality in cirrhosis …”
mentioning
confidence: 99%